The Effect of Cooperative Model Type Team Assisted Individualization (TAI) on Student Learning Outcomes in Integrated Thematic Learning - Putri, Sonia Dwi Permata; Fitria, Yanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2022)
The main objective of this study is to identify the impact of Team Assisted Individualization models on the academic results of primary school students on the topic